Command-control for Real-time Systems. - Chadli, Mohammed (ISTE., 2013)
A real-time system is a complex system which is an integral part of an industrial or experimental system, a vehicle or a construction machine. The peculiarity of these systems is that they are driven by real-time targets in distributed environments.Command-control for Real-time Systems presents the calculation of correction for industrial systems of different physical natures, their implementation on real-time target industrial systems (PLC-SCADA, embedded systems with distributed networks, Networked Control Systems) and their validation by simulation. It optimizes industrial p.